2012
DOI: 10.1002/pds.3321
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Guillain–Barré syndrome after meningococcal conjugate vaccination

Abstract: Among members of five US health plans, MCV4 vaccination was not associated with increased GBS risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…A peak in incident cases occurring during late winter and early spring has been reported and might be explained by the seasonality of preceding infections triggering the development of GBS [8,9]. Furthermore, GBS has been suggested as a severe adverse reaction to several vaccines [2,10,11,12,13,14,15,16,17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…A peak in incident cases occurring during late winter and early spring has been reported and might be explained by the seasonality of preceding infections triggering the development of GBS [8,9]. Furthermore, GBS has been suggested as a severe adverse reaction to several vaccines [2,10,11,12,13,14,15,16,17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…There is no increased risk of Guillain-Barre syndrome associated with vaccine use, although vigilance for this adverse effect is essential. 20 Immunogenicity studies of MCV4 have shown that it is safe and effective to give concomitantly with other childhood vaccines such as measles, mumps, rubella, varicella and the pneumococcal conjugate vaccine. 21 …”
Section: Meningococcal Vaccines Registered In South Africamentioning
confidence: 99%
“…With the exception of early rabies vaccines, development of GBS following vaccination is extremely rare, indicating that other host-specific factors, including genetic polymorphisms are likely to be important. The risk of developing GBS following immunization with oral polio vaccine [113], Menactra ® (Sanofi Pasteur, Paris, France) meningococcal conjugate vaccine (MCV4) [114], tetanus toxoid containing vaccines [115], yellow fever vaccine (17D-204) [116] or against measles mumps and rubella [117], hepatitis B virus [118,119], H. influenzae type b [120], Japanese encephalitis [120] or small pox [121] is probably very low. Early influenza and rabies vaccines on the other hand have been shown to increase risk and are discussed in more detail below.…”
Section: Vaccinationmentioning
confidence: 99%